Institusionalisasi Pendidikan Politik PDI Perjuangan Dalam Sekolah Partai Bagi Calon Kepala Daerah 2020 - Hasibuan, Shahril; Ma’riyah, Chusnul (STISIPOL Raja Haji, 2022)
The School of Party is the strategies design for PDI Perjuangan to prepare the political leadership for the regional head through simultaneous local elections. The simultaneous regional elections in the midst of the Covid-19 pandemic, the practice of oligarchic and dynastic politics, as well as the presidential threshold rules make the parties flock towards a vote-seeking orientation and oriented towards official-seeking so that political parties do not lead to increasing the capacity of cadres and members of the party. alone. The results of this author's research through the process of in-depth interviews and written statements from resource persons. By using qualitative methods in the form of case studies. By using the concepts of Gunther and Diamond (2001; 2003), Wolinetz (2002) regarding the types and functions of political parties in designing political institutions with party policies in the theory of design institutions (institutional design) Goodin (1998. Party school as a PDI Perjuangan’s design in preparing and produce the regional leadership to be in line with the President, which is of course in line with the PDI Perjuangan, because the President is a party official from the PDI-P. This is because the 2020 simultaneous regional head elections will form a coalition. The Party School becomes a design institution, namely the creation of a design. PDI Perjuangan's vision and mission to be able to uniform regional and central policies as PDI Perjuangan's policy with its ideological aspects.